(untitled) (Práxis Educativa, 2024)
This text is a bibliographical investigation that intertwines education policies, school curriculum and educational assessment in the context of the Sistema de Avaliação da Educação Básica (SAEB) [Basic Education Assessment System]. The general objective was to understand the implications of the SAEB external assessment produced in the pedagogical practice of teachers in the 5th grade of Elementary School, in experiences that precede the application of the test and that have had an intense impact on their work rhythm, feelings of affectation, greatly influencing the constitution of teaching subjectivity. The results elucidate that the narration of daily teaching experiences represents a powerful way of possible curricular texts, which privilege the construction of knowledge and awareness guided by an established rationality of training, in addition to the hegemonic logics of the evaluation systems that occur in public schools in Basic Education. Keywords: External assessments. Curriculum. Teacher training.